2018
DOI: 10.1186/s40364-017-0115-6
|View full text |Cite
|
Sign up to set email alerts
|

SALL4 as a transcriptional and epigenetic regulator in normal and leukemic hematopoiesis

Jianchang Yang

Abstract: In recent years, there has been substantial progress in our knowledge of the molecular pathways by which stem cell factor SALL4 regulates the embryonic stem cell (ESC) properties, developmental events, and human cancers. This review summarizes recent advances in the biology of SALL4 with a focus on its regulatory functions in normal and leukemic hematopoiesis. In the normal hematopoietic system, expression of SALL4 is mainly enriched in the bone marrow hematopoietic stem/progenitor cells (HSCs/HPCs), but is ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 114 publications
0
34
1
Order By: Relevance
“…Here we demonstrated that Salm is continuously required for correct sarcomere morphogenesis, as late salm knock-down leads to defects in sarcomere growth during the late sarcomere maturation phase, causing severe muscle atrophy in adults. It might do so by modifying the cooperation between Mef2 and E2F or by changing chromatin states, as vertebrate spalt homologs are recently discussed as epigenetic regulators ( Yang, 2018 ; Zhang et al, 2015 ). However, Salm cannot be solely responsible for the transcriptional transition after 30 hr APF, as the transition still partially occurs in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…Here we demonstrated that Salm is continuously required for correct sarcomere morphogenesis, as late salm knock-down leads to defects in sarcomere growth during the late sarcomere maturation phase, causing severe muscle atrophy in adults. It might do so by modifying the cooperation between Mef2 and E2F or by changing chromatin states, as vertebrate spalt homologs are recently discussed as epigenetic regulators ( Yang, 2018 ; Zhang et al, 2015 ). However, Salm cannot be solely responsible for the transcriptional transition after 30 hr APF, as the transition still partially occurs in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent and novel genetic mutations are increasingly discovered through FISH, PCR and next-generation sequencing studies of leukemia specimens [1][2][3][4][5]. These findings led to new classifications of leukemia [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…We first analysed the surface expression of CD68 and HLA-DR, markers expressed by macrophages. [23] Fibroblast-conditioned medium HKSA decreased the level of These results were correlated with the number of cells expressing macrophage marker CD68 ( Figure 3B-C). Under both treatments, we observed two populations that were discriminated by their level of CD14 expression: CD14 high CD68 + and CD14 low CD68 + .…”
Section: Monocytes Exhibit Pro-inflammatory Responses Towards Hksamentioning
confidence: 63%